Empowering Obese Children in Physical Education: Exploring the Influence of Verbal Encouragement on Games Intensity, Mood States, and Physical Enjoyment during Passing Games - Bilel Aydi; Okba Selmi; Bruno E. Figueira; Mohamed Abdelkader Souissi; Bruno Gonçalves; Katsuhiko Suzuki; Beat Knechtle; Che-Yi Yang; Yung-Sheng Chen; Nizar Souissi (PLoS ONE, 2025)
This study aimed to assess the impact of physical education teachers’ verbal encouragements on the psychophysiological aspects, physical enjoyment, and mood states of obese children (OC) in a physical education context. Sixteen OC students (mean age = 13.81 ± 0.73 years) from a preparatory school participated in two test sessions, conducted in a randomized order. Each session involved a series of passing games (games of 10 successive passes) with and without verbal encouragement, with a one-week interval between sessions. The games, formatted as 3 vs. 3 with two additional obese joker’ players, lasted 18 minutes. Each game comprised four 3-minute active periods interspersed with 2-minute passive recovery bouts, played on a 10 × 20-m pitch. Heart rate was continuously measured throughout each session. Additionally, the Brunel Mood Scale (BMS) was assessed before and after the PG. Furthermore, rating of perceived exertion (OMNI-RPE) and physical activity enjoyment (PACES) were assessed after the testing sessions. Video analysis was used to quantify technical actions during PG. PGs with VE induced higher HR (% maximum HR and mean HR), OMNI-RPE, and PACES scores than PGs without VE (ES=−1.51, ES=−0.78, ES=−0.73, ES=2.07, respectively). Compared with PGs without VE, SSGs with VE resulted in an increased percentage of successful passes, number of Goal (10 passes) and fewer lost balls (ES=O.70, ES=−0.54, ES=−0.86, respectively). The PGVE trial also showed higher vigor and lower total mood disturbance (TMD) compared to the PGNVE trial (ES = −1.11, d = 0.78, respectively). Physical education teachers are encouraged to incorporate joker exercises with verbal encouragement to enhance game intensity, mood state, physical enjoyment and technical performance during games among OCs.